PENERAPAN IMMUNITY RIGHTS KEPALA NEGARA DI HADAPAN INTERNATIONAL CRIMINAL COURT (ICC) DITINJAU DARI SEGI HUKUM INTERNASIONAL (Studi Kasus Upaya Penangkapan Presiden Sudan Omar Al-Bashir oleh ICC) - Putra Fajar Rulandika (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
The impunity enjoyed by state officials is part of the freedom to act given by the stategovernment. The development of the right of immunity and its deviation attract moreinternational legal observers, especially in the most recent case that happened to SudanesePresident Omar al-Bashir. As the incumbent president of Sudan, Omar al-Bashir is accusedby the Prosecutor of the ICC (International Criminal Court) Luis Moreno-Ocampo hascommitted genocide, crimes against humanity and war crimes in Sudan. The accusation isthen developed with the issuance of arrest warrant against Omar al-Bashir by the ICC. Theproblem is: How can the application of the right of the head of state immunity in internationalcriminal tribunal in terms of international law? Is Letter to the ICC Arrest Omar al-Bashiras the head of state legal under international law?In an effort to identify and analyze the problems above, the writer used normativejuridical approach is to see the contents of a rule in international law concerning immunity(immunity) front of the heads of state in The International Criminal Court. By using materialsthat existing law analysis techniques the author uses descriptive analysis of legal materials.Based on the research results, obtained answers to existing problems, that the rightof immunity for heads of state accused of international crimes will not affect the exercise ofjurisdiction the International Criminal Court (ICC). This is because international crimesprovided for in the ICC confirms the necessity of individual accountability mechanisms. RomeStatute 1998, as the main foundation of the ICC, individual accountability mechanismsagainst international crime. Therefore immunity, both for state officials and heads of state,can not affect the exercise of jurisdiction of the ICC. The authority is regulated in the articlesof the statute. Especially in the case of international crimes are regulated, namely genocide,crimes against humanity, war crimes, and crimes of aggression.The process of arrest against Omar Al-Bashir has met the requirements prescribedby the Rome Statute 1998. The filing of cases by the UN Security Council which is based onarticle 13 (b), allows the ICC yurisdiction apply, in this case in Sudan. Detention its elf isdone for smooth judicial process by taking into account Article 58 of the Rome Statute.Keywords: Immunity Rights, the International Criminal Court, International Law.